The Lord's Supper as the sign and meal of the New Covenant - Waters, Guy Prentiss, 1975- (Short studies in biblical theology., 2019)
"This book seeks to help Christians recover the importance of the Lord's supper in the Christian life by explaining three purposes of the sacrament in light of God's covenant signs"--